Healthy food consumption in the Covid-19 era: Empirical evidence from Italian consumers choices on functional products - Dell'Unto, Davide; Meccariello, Giulia; Cortignani, Raffaele (Economia agro-alimentare/Food Economy - Open Access, 2023)
This study provides an explorative analysis of the potential appreciation manifested by 312 Italian consumers for functional confectionery products, obtained from high-amylose soft wheat flours (high-amylose confectionery products, HACPs). An online questionnaire was administered in 2021, which assessed respondents’ willingness to pay (WTP) a premium price for HACPs with respect to non-functional confectionery products. Detailed information about respondents and their families was collected and put in relation with the willingness, or not, to pay a premium price for HACPs through a Binary Logit model. Two thirds of respondents were willing to pay a premium price for HACPs, that stood at +12.3%. Analysis of the results of the Binary Logit model led to highlight that respondents’ WTP for HACPs is positively influenced by age, level of family income, satisfaction with the latter during the COVID-19 pandemic, habit to purchase food products on e-commerce channels, adoption of healthy eating styles and belief that functional foods can contribute to improve well-being. At the opposite, respondents’ WTP is negatively influenced by family size, presence of dependent members and, interestingly, habit to practice physical activity with high frequency. Based on these findings, useful insights also in support of confectionery industry and commercial distribution are finally reported.